The Effects Of Job Satisfaction And Leader Supportiveness Behavior On Altruistic Organizational Citizenship Behavior - Yusoff, Mohamad Nordin (2002)
This study examines the effects of job satisfaction and leader supportiveness behavior on altruistic OCB. This research also examines the moderating effects of demographic variables (age, gender, and race) on the relationship between of the independent variables (job satisfaction and leader supportiveness behavior) and altruistic OCB. Data in this study were obtained from a total of 96 academic staff attached to 12 centers of studies (schools) in a public institution of higher learning in Malaysia.